State of somatic features and motor capacity 14-year players with secondary Polish Nobel Prize winners in Więcbork - Paweł Mucha; Marek Napierała; Małgorzata Pezala; Walery Zukow (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2015)
The aim of the study was to compare the characteristics of somatic and motor skills among young people in sport class and the class of general-Gymnasium in Wiecbork. The results were compared to the results of the regional and national studies. The tests were subjected to 40 - students aged 14 years (20 with class sports, and 20 general-class) of Gymnasium. Polish Nobel Prize winners in Wiecbork. The study of motor skills were six trials of the International Physical Fitness Test. Sports Group proved to be better in each of the trials compared motor skills of the students.